Analysis of Bioactive Components and In-Silico Study of Ethanol Extract from Eleutherine Bulbosa (Mill.) Urb. (Bawang Dayak) using UHPLC-MS Method: Analisis Komponen Bioaktif dan Kajian In Silico Ekstrak Etanol Dari Eleutherine bulbosa (Mill.) Urb. (Bawang Dayak) dengan Metode UHPLC-MS - Indah Hairunisa; Afin Irgi Prasetyo; Dinda Kholifatul Awalia; Ferdi Kurniawan; Dwi Lestari; Mohd Fadzelly Abu Bakar (JRST (Jurnal Riset Sains dan Teknologi), 2026)
Breast cancer is one of the most common non-communicable diseases in Indonesia that characterized by uncontrolled growth of abnormal cells. The high incidence and mortality rates associated with this disease have driven the search for new anticancer agents, including those derived from natural sources such as Eleutherine bulbosa (Mill.) Urb. (Dayak onion). The bulbs of the Dayak onion are known to contain bioactive compounds such as flavonoids and naphthoquinones, which may possess anticancer activity. This study aims to identify secondary metabolites from Dayak onion ethanol extract using UHPLC-MS, as well as evaluate the ADMET profile (Absorption, Distribution, Metabolism, Excretion, and Toxicity) and in silico activity of the identified compounds against the HER2 receptor (Human Epidermal Growth Factor Receptor 2). The results of the UHPLC-MS analysis revealed the presence of 233 compounds in the Dayak onion ethanol extract, with 23 compounds showing the highest reactivity. After screening based on the Lipinski Rule of Five criteria, as well as ADME and toxicity predictions, one potential candidate compound was identified: 5-O-Methylvisamminol. This compound meets all the physicochemical profile criteria (Lipinski’s Rule of Five) for oral drugs and exhibits a satisfactory pharmacokinetic profile with an HIA value of 95.7%; Caco-2 cell permeability of 39.7 nm/s; PBB of 72.1%;  BBB 0.814, and through the Ames test, this compound was also found to be non-mutagenic and non-carcinogenic. Molecular docking analysis showed that 5-O -Methylvisamminol has a binding energy (∆G) of -9.1 kcal/mol when interacting with the HER2 receptor and can interact with five key amino acids (ASP863, LEU852, VAL734, LEU796, and LEU800) through hydrophobic interactions. The compound 5-O-Methylvisamminol is predicted to have potential as an anti-breast cancer agent that can target HER2.   ABSTRAK (Bahasa Indonesia) Kanker payudara merupakan salah satu penyakit tidak menular yang paling sering ditemukan di Indonesia yang ditandai oleh pertumbuhan sel abnormal yang tidak terkendali. Tingginya angka kejadian dan kematian akibat penyakit ini mendorong pencarian agen antikanker baru, termasuk dari bahan alami seperti Eleutherine bulbosa (Mill.) Urb. (bawang dayak). Umbi bawang dayak diketahui mengandung senyawa bioaktif seperti flavonoid dan naftokuinon yang berpotensi memiliki aktivitas antikanker. Penelitian ini bertujuan untuk mengidentifikasi metabolit sekunder dari ekstrak etanol bawang dayak menggunakan metode UHPLC-MS, serta mengevaluasi profil ADMEToks (Absorpsi, Distribusi, Metabolisme, Ekskresi, dan Toksisitas) dan aktivitas in silico dari senyawa teridentifikasi terhadap reseptor HER2 (Human Epidermal Growth Factor Receptor 2). Hasil dari analisis UHPLC-MS menunjukkan adanya 233 senyawa dalam ekstrak etanol bawang dayak, dengan 23 senyawa yang menunjukkan reaksi paling tinggi. Setelah dilakukan pemilahan berdasarkan kriteria Lipinski Rule of Five serta prediksi ADME dan Toksisitas, diperoleh satu kandidat senyawa potensial, yaitu 5-O-Methylvisamminol. Senyawa ini memenuhi semua kriteria profil fisikokimia (Lipinski Rule of Five) untuk obat oral dan menunjukkan profil farmakokinetik yang cukup baik dengan nilai HIA 95,7%; sel Caco-2 39,7 nm/detik; PBB 72,1%;  BBB 0,814 dan melalui uji Ames senyawa ini juga tidak bersifat mutagenik maupun karsinogenik. Analisis molecular docking menunjukkan bahwa 5-O-Methylvisamminol memiliki energi pengikatan (∆G) sebesar -9,1 kkal/mol ketika berinteraksi dengan reseptor HER2, serta mampu berinteraksi dengan lima asam amino kunci (ASP863, LEU852, VAL734, LEU796, dan LEU800) melalui interaksi hidrofobik. Senyawa 5-O-Methylvisamminol diprediksi memiliki potensi sebagai agen antikanker payudara yang dapat menargetkan HER2.